Diabetic Retinopathy Treated with Laser Photocoagulation and the Indirect Effect on Glycaemic Control - Anna Praidou; Sofia Androudi; Periklis Brazitikos; George Karakiulakis; Eleni Papakonstantinou; Ioannis Tsinopoulos; Stavros Dimitrakos (Journal of Diabetes Research)
Purpose. To identify any possible relation between glycaemic control and previous laser photocoagulation for diabetic retinopathy. Methods. Seventy-two patients with diabetes were included in the study and were separated into 2 groups according to previous treatment (group A) or not (group B) with argon laser photocoagulation. Glycaemic control was estimated by measuring blood levels of HbA1c in four consecutive measurements. Results. Blood levels of HbA1c in group A were significantly lower 3, 6, and 12 months after laser treatment as compared to blood levels of HbA1c before laser treatment (7.1±0.4% versus 7.6±0.9%, 7.2±0.2% versus 7.6±0.9%, and 7.1±0.2% versus 7.6±0.9%, resp., all P<0.05). Blood levels of HbA1c in group B did not differ significantly in four consecutive measurements. Conclusion. Our results suggest that we should anticipate a better glycaemic control in cases of patients with diabetes previously treated with laser photocoagulation.